Policy Learning in Innovation Policy: A Comparative Analysis of European Union Member States - Mart Laatsit (Copenhagen Business School (CBS), 2019)
This thesis studies policy learning in the field of innovation policy. In particular, I look at the sources of policy learning, with a focus on evaluations and informal networks. I provide a comparative perspective across European Union (EU) member states on how they use these sources for policy learning. As such, this thesis is guided by the research question “what are the differences across countries regarding the way in which they use various sources of policy learning”. The current literature on policy learning contains three important gaps. There is a lack of systematic attention to the sources of policy learning, coupled with a lack of conceptual understanding of these sources. In addition, there is a lack of empirical cross-country studies on how these sources are used in different national contexts. With this thesis and its three consisting articles, I address these challenges. In the first article I analyse evaluations a source of learning and provide an empirical overview of the extent to which EU countries have developed systemic approaches for policy evaluation. In the second and third article I study networks as a source of learning by mapping the informal networks of policy makers and analysing the proximity factors behind these networks. The thesis is based on the theory of policy learning. This theory emphasises the role of knowledge in the process of policy-making, offering an alternative to the power-based explanations of policy change. Policy learning can have different sources – some approaches stress the importance of sophisticated analytical tools, others focus on learning from peers through network connections. In this thesis, I look at one example from both strands. On the one hand, I study how evaluations are used a source of learning, by developing the concept of `system oriented innovation policy evaluation'. On the other hand, I analyse how countries learn from their peers through informal networks. The empirical focus of the thesis is on innovation policy in EU member states. Over the recent decades innovation policy has occupied a prominent position in the EU and several initiatives have been launched to enhance policy learning within and between member states. In order to gather data on the use of the two sources for learning, interviews were carried out with senior policy makers from the 28 member states. In addition, policy documents and international databases were used to complement the interview data on evaluations. This information was subsequently used to develop an overview of the evaluation practices in all 28 countries and to map the informal networks between policy makers.
hdl:10398/9704
Keywords: 650